MEMPERKOKOH BASIS TEOLOGIS PENDIDIKAN ISLAM - Sauqi Futaqi (TA'LIM : Jurnal Studi Pendidikan Islam, 2020)
Islamic education cannot be separated from its theological basis. The theological basis of Islamic education comes from Islam itself. Nevertheless, the theological building for the conceptualization of Islamic education is lacking - not to say no at all - finding its relevance in the Islamic educational scene so far. Generally the discourse of Islamic education is directed at developing theories, methodologies, and speaking very little about philosophy in its deep understanding. The link between Islamic theology and education lies in the beliefs, spirits and values ​​that have strengthened progress in the field of education. This is to avoid spiritual anxiety amid the complexities of global progress. This anxiety can be seen from a number of national education curriculum contents that are now beginning to be directed to strengthen the spiritual and social aspects, without reducing the scientific ethos in the field of Science and Technology. At least the development of Islamic education theology discourse can present a new ethos for the integrity of the process of human life as the subject of education.